Інформаційна технологія прогнозування фінансових результатів страхових компаній - Березька, К. М.; Кнейслер, О. В.; Спасів, Н. Я.; Кулина, Г. М.; Berezka, K. M.; Kneysler, O. V.; Spasiv, N. Ya.; Kulyna, H. M. (Видавництво Львівської політехніки, 2021)
Використано економетричні екстраполяційні методи дослідження. Проаналізовано наукові роботи, пов'язані з екстраполяційними методами прогнозування часових рядів. Проаналізовано динаміку формування фінансових результатів страхових компаній України за видами їх діяльності. Визначено основні чинники, що визначають результативність. З'ясовано, що найбільш раціональним підходом до короткотермінованого прогнозування фінансових результатів страховиків є застосування експоненційного згладжування. Вибрано оптимальні параметри для моделі експоненційного згладжування методом на сітці. Використано такі показники якості моделі: середнє значення середньоквадратичного відхилення помибки моделі до фактичних даних, коефіцієнт розбіжності Г. Тейла, середню абсолютну відсоткову помибку МАРЕ. Спрогнозовано чистий фінансовий результат діяльності страховиків України і його довірчий інтервал для рівня надійності 0,95. Результати прогнозування, що базуються на застосуванні економетричного моделювання, дають змогу виявити перманентні позитивні зрушення на вітчизняному страховому ринку та діяльності страховиків на ньому; підтвердити ефективність прийнятих стратегічних і тактичних фінансових рішень страхових компаній; підвищити ефективність господарювання страховиків за підсумками кількісного визначення ступеня впливу кожного із чинників на формування фінансових результатів їх діяльності; окреслити тенденції розвитку ситуації в майбутньому, точніше формувати комплекс заходів щодо максимізації прибутку та мінімізації витрат страхових компаній для забезпечення гарантій надійного страхового захисту та задоволення інтересів їх власників.

The purpose of time series modelling is to predict future indicators based on the study and analysis of past and present data. Various time series methods are used for forecasting. The article uses econometric extrapolation research methods. Analyzed scientific works are related to extrapolation methods for forecasting time series. The dynamics of the financial formation related to results of Ukrainian insurance companies by the types of their activities have been analyzed. The main factors that determine the effectiveness are determined. It was found that the most rational approach to short-term forecasting of the financial results of insurers is the use of exponential smoothing. The optimal parameters are selected for the model of exponential smoothing of the first and second order by the method on the grid. The following indicators of the quality of the model were used: the mean value of the standard deviation of the model error to the actual data, Theils coefficient of discrepancy, mean absolute percentage error MARE. The net financial result of the activities of Ukrainian insurers was predicted, the lower and upper bounds of the forecast for 2021 for a reliability level of 0.95. To predict the net financial result of the activities of Ukrainian insurers, statistical data for 10 years from 2011 to 2020 were used, the financial results of the main (insurance and other operating) activities before tax, the results of financial activities before tax, the financial results of other ordinary activities (extraordinary events) before tax, incometax. The prototype of the software module for predicting the financial performance of insurance companies was developed in Statistica and Excel. Forecasting results based on the use of econometric modelling make it possible to identify permanent positive shifts in the domestic insurance market and the activities of insurers on it; to confirm the effectiveness of the adopted strategic and tactical financial decisions of insurance companies; to increase the efficiency of insurers management based on the results of quantitative determination the degree of influence of each factor on the formation of the financial results related to their activities; to identify trends in the development of the situation in the future, to more accurately form a set of measures to maximize profits and minimizecosts of insurance companies to ensure guarantees of reliable insurance protection and satisfy the interests of their owners.
Information technology for forecasting the financial results of insurance companies
Keywords: фінансові результати; страхові компанії; чистий фінансовий результат; експоненційне згладжування; часовий ряд; економетричні методи прогнозування: financial results; insurance companies; net financial result; exponential smoothing; time series; econometric forecasting methods